(untitled) (European Journal of Pedagogical Initiatives and Educational Practices, 2024)
The article examines the influence of the novels of F.M. Dostoevsky on the work of the American writer Donna Tartt. The writer actively uses allusions to Russian literature, reinterpreting their plot and adding new meanings. Perception of F.M. Dostoevsky’s works is manifested through narration and intertextuality, which perform several functions in the novel: plot-forming, compositional and ideological.